Interdisciplinary model transfer and realism about physical analogy. - Tan, Peter (Synthese, 2023)
Model transfer is the scientific practice of taking a model which was initially applied in one particular kind of target system in some particular scientific domain and applying it to represent a novel target system in a novel scientific domain. This paper motivates a realist interpretation of empirically successful model transfers and the implications of such an interpretation for the metaphysics of science. The paper uses two examples of empirically successful model transfer, the first of which is a strikingly successful recent application of the Ising model to neurobiology, the second of which is Maxwell’s “method of physical analogy”. The paper first defends the need for a realist picture regarding the transfer of model templates and the apparent discovery of physical analogies. Then, it examines further the implications of such a picture, finding it to be quite revisionary in its conception of the nature of causal processes.